Tool-Assisted Manual Testing : A Case Study: Test Data Configuration Tool in a Medical Software Company - Zafar, Sohaib (My University, 2024)
The objective of this study was to research tool-assisted manual testing using a case study of a test data configuration tool in a medical software company. A comprehensive literature review was undertaken to gain insights into the fundamental concepts of software testing, manual and automated testing, software testing tools, and the various roles involved in software testing. In-depth interviews were conducted to identify the challenges Software Quality Engineers (SQEs) encountered in the current testing process. To address those challenges, we investigated different options and compared them to determine the most suitable process for automating the test data configuration when a new database server is taken into use for testing the medical software. Finally, we gathered feedback from twelve manual testers through a survey regarding the selected test data configuration tool and related processes. The main findings from this survey indicate that the tool has the potential to assist testers in their testing activities by eliminating repetitive steps involved in importing test data to the database server. We also made suggestions for future research, highlighting the need to develop new scripts to automate tasks not currently covered by the tool.
Keywords: software testing, tool-assisted manual testing, automated testing, hybrid testing, software testing in the medical software company